Reduction of Power consumption due to modernization of technological drying process Using Drying Agent Recirculation - A. V. Kochetkov; E. G. Migoutsky; V. A. Sednin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains an analysis of influence on heat consumption (in the drying processes with the help of flue gases  in mixture with air) such parameters as modes of drying agent recirculation, recirculation coefficient and possible ranges of its values for selection of optimum parameters of this quantity are considered in the paper.